1997
DOI: 10.1111/j.1439-0531.1997.tb01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryopreservation on Bovine Sperm Viability as Determined by Dual DNA Staining

Abstract: : Living and dead spermatozoa were examined for the effects of sperm concentration level on sperm viability. Semen was collected from two different bulls on each of four collection dates. A ninth bull was collected on all four collection dates as a control for effects of collection date. The ejaculates from these nine bulls were diluted to 30 × 106 spermatozoa/0.5 ml and then serially diluted to 20, 10, 5, or 1 × 106 spermatozoa/0.5 ml French straw. One‐half of the straws for each dilution series was stored 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…Although both studies used twelve bulls, the mean percentages of JC-l-stained sperm + SEM and post-thaw motility + SEM in the present study were 47. 9 3.3 and 71.7 + 1.3, respectively; the same values in the previous study were 59.0 + 7.4 and 65.8 + 5.8, respectively. The reason for the difference was obvious when one compared the two scatter plots (not shown).…”
Section: Sybr-14asupporting
confidence: 61%
See 2 more Smart Citations
“…Although both studies used twelve bulls, the mean percentages of JC-l-stained sperm + SEM and post-thaw motility + SEM in the present study were 47. 9 3.3 and 71.7 + 1.3, respectively; the same values in the previous study were 59.0 + 7.4 and 65.8 + 5.8, respectively. The reason for the difference was obvious when one compared the two scatter plots (not shown).…”
Section: Sybr-14asupporting
confidence: 61%
“…Dot plots of SYBR-14/PI-stained spermatozoa showed three populations [9], as did JC-1/PI dot plots (Fig. 1).…”
Section: Fluorometric Evaluationsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, the dilution of the ejaculates reduces the concentration of seminal plasma antioxidants. Previous studies (Garner et al, 1997 and2001) showed that the volume and sperm concentration of the ejaculates and the final concentration of the seminal plasma in the extended semen have important roles in plasma membrane and acrosome intact sperm after thawing of the cryopreserved sperm. Garner et al (2001) suggested that the source of the effect was seminal plasma.…”
Section: Relationships Of Antioxidant Concentrations On Sperm Qualitymentioning
confidence: 99%
“…Studies regarding the pathophysiology of human sperm function have indicated that oxidative stress generated by mitochondrial activity in human sperm may be a potential cause of reduced human male fertility [26,34]. In addition, a correlation between sperm motility and mitochondrial activity has been reported in studies with equine [35], human [36], and bovine spermatozoa [37]. Nonetheless, a correlation with NRRs could not be established in bull spermatozoa [38], possibly because mtDNA is maternally inherited and selective pressure would not affect the male lineage [39].…”
mentioning
confidence: 98%